Preparation, Structural Identification, and Biomedical Evaluation of Some New Complexes - Abbas, Alyaa Khider; Fadhil, Asmaa Edrees (Indonesian Journal of Chemistry, 2024)
A new nano azo ligand, [2-amino-6-oxo-6,7-dihydro-1H-purin-8-yl)diazenyl)nitrobenzene (AH), and its Ag(I), Cu(II), and Zn(II) complexes were successfully synthesized and characterized using elemental analyses, magnetic susceptibility, molar conductance, and spectroscopic techniques (FTIR, UV-vis, ¹H-NMR), along with thermal analysis. FTIR confirmed the ligand acts as a neutral N,N-bidentate. The metal-to-ligand ratio was determined to be 1:1 for Ag(I) and Zn(II) complexes and 1:2 for the Cu(II) complex. Stability constants and Gibbs free energy, assessed via spectrophotometry, indicated high stability for all complexes. SEM and X-ray diffraction revealed nanoscopic properties for the Ag(I) and Cu(II) complexes. The antimicrobial activity against Staphylococcus aureus, Klebsiella pneumoniae, and Candida albicans species showed good efficiency compared to reference drugs. The ligand also exhibited moderate antioxidant activity using the DPPH assay. Additionally, the Zn(II) complex demonstrated effective anti-inflammatory activity, promoting wound healing within 14 days, compared to 16 days with silver sulfadiazine and 18 days without treatment.